Effect of Addition Egg Shell Flour to Physical Properties of Dangke Whey Ice Cream - S. Sumarni; Rajmi Faridah; Andi Kurnia Armayanti (Chalaza Journal of Animal Husbandry, 2023)
The physical properties of whey dangke which is more dilute than whey required other additional ingredients in making ice cream. The material that can be used is eggshell flour. This study aims to determine the effect of the addition of eggshell flour on the physical properties (overrun and melting resistance) of whey dangke ice cream. This research was conducted at the Animal Husbandry Laboratory, Faculty of Agriculture, Muhammadiyah University of Sinjai. This study used a completely randomized design (CRD) with 4 treatments with 3 replications. The treatment given was the addition of chicken eggshell flour to whey dangke ice cream. P0: 0% eggshell flour, P1: 2% eggshell flour, P2: 4% eggshell flour, P3: 6% eggshell flour. The results of this study indicated that the addition of eggshell flour to whey dangke ice cream had a significant effect on physical properties, namely overrun and melting resistance.